An overview of water markets in southern Africa: an option for water management in times of scarcity - Matchaya, Greenwell C.; Nhamo, Luxon; Nhlengethwa, Sibusiso; Nhemachena, Charles (MDPI, 2019)
Southern Africa faces acute water scarcity challenges due to drought recurrence, degradation of surface water resources, and the increasing demand of water from agriculture, which has to meet the growing food demands of an increasing population. These stressors require innovative solutions that ensure the sustainability of water resources, without which the consequences could be dire for a region exposed to a host of vulnerabilities, including climate change. This review outlines the role of water markets in water management in times of water scarcity, highlighting the drivers of water markets in southern Africa, such as water scarcity, transboundary nature of water resources, and their uneven distribution. The review further discusses the role of water markets in climate change adaptation. Related institutional and legal frameworks as well as water allocation mechanisms are explored, aiming at improving water markets governance. The impact of adaptation to new water regimes in the face of scarcity are assessed by considering characteristics of current markets as related to future opportunities. In a diverse region such as southern Africa with unevenly distributed water resources, advancing the concept of water markets could play an important role in mitigating water scarcity challenges and promoting regional integration through coordinated transboundary water transfers. The emergence of water markets in the region is influenced by the continued depletion of water resources, which is resulting in the adoption of innovative water marketing strategies, such as inter-farm sharing or farm joint venture systems and inter-basin and intra-basin water transfers. As the concept is new in the region, it still has challenges that include general market inefficiencies, high transaction costs, market information asymmetries, imperfect competition, and weak or absent robust institutional frameworks that can facilitate market development.